Strategizing in an inter-organizational setting: The case of a~German healthcare partnership - Henrike Schmidt; Eva-Maria Wild; Claus D. Jacobs; Rudolf Blankart (Schmalenbach Journal of Business Research (SBUR), 2025)
Solving complex societal problems requires collaboration across organizational boundaries. Such collaboration inherently involves strategizing across these boundaries, which is linked to a~high degree of complexity and ambiguity. Despite its critical relevance, there is a~paucity of empirical studies on the practices of inter-organizational strategizing. To address this research gap, we conducted a~longitudinal case study of a~healthcare partnership in a~major metropolitan city of Germany involving eleven different organizations. Operating in a~socially deprived area, the healthcare partnership aimed at tackling the problem of poor health outcomes arising from a~lack of alignment among providers and payers of healthcare. Drawing on a~rich data set of our single case study, we analysed the different phases of a~strategizing process from 2012 to 2019. We identify and propose three core practices of inter-organizational strategizing that influence strategic alignment: structuring conflicts, gaining commitment, and agreeing on objectives. Our results also suggest the presence of two distinct modes of strategizing that relate to these practices, one characterized by exclusiveness and the other by inclusiveness. Further theorizing from these findings leads us to propose that these practices and the modes of strategizing interrelate and ultimately result in either strategic alignment or strategic disorder. Our findings are particularly relevant to strategy and policy-makers who are faced with the challenge to solve wicked problems.
Keywords: I1; L1; M1; 650; Cross-sector; Healthcare; Inter-organizational collaboration; Participation in strategy-making; Strategy formation